PENGARUH MODEL PEMBELAJARAN SUGESTI IMAJINASI TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS X SMA NEGERI 48 JAKARTA - Rida Tania Noviani; Nur Amalia; Nur Aini Puspitasari (Prosiding Seminar Nasional Berseri, 2020)
This study aims to determine the effect of learning outcomes in writing poetry using imagination suggestion learning models in class X students of SMA 48 Jakarta in the second semester of the academic year 2018-2019. The research method used is a quantitative research method with a research design Pretest-Posttest Control Group Design. The sample used is Simple Random Sampling. In the experimental class obtained Lcount = 0.13 <0.15 = Ltable at a significant level of 0.05 and the control class Lcount = 0.14 <0.15 = Ltable at a significant level of 0.05. In both of these samples it turns out Lcount<Ltable, it can be concluded that the two samples are normally distributed. The homogeneity test of the test results using the fisher test, obtained Fcount = 1.31 <1.76 = Ftable, it turns out Fcount<Ftable then it can be concluded that the sample is homogeneous. Furthermore, hypothesis testing using t-test obtained Tcount = 7.14> 1.67 = Ttable at a significant level of 0.05 turns out Tcount> Ttable then H0 is rejected and H1 is accepted. That is, there is a significant influence by using the imagination suggestion learning model on the ability to write poetry of class X students of SMA 48 Jakarta